Strengthening of variational thinking through a mediated intervention with the use of ICT for ninth grade students - Martínez-López, Leonardo Geiner; Gualdrón-Pinto, Elgar (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article reports the findings of a qualitative study done within the Mathematics field focused on the development of the variational thinking in ninth grade students (14 to 17 years old) through the use of didactic sequences for this purpose and mediated through ICT. This research was carried out in three phases: First, an initial diagnosis that aimed to identify the level of pre-knowledge in arithmetic and variational thinking based on the indicators established in the knowledge test. Then, an intervention was made by designing didactic sequences which were adapted to the institutional mathematics curriculum, including learning activities towards the analysis of some variation and change cases. Lastly, a final diagnosis evaluated the level reached by the group of students. The analysis of the results allows us to conclude that the intervention generated meaningful changes within the group of participants related to their variational thinking.